Analysis of the Addition of CMC to Biodegradable Plastics from Banana Hump - Chairul Amni; Ismet Ismet; Irmayanti Irmayanti; Joli Supardi; Miftahurrahmah Miftahurrahmah (Universitas Serambi Mekkah, 2022)
The use of banana hump flour as a raw material for making biodegradable plastic is an alternative to using banana starch plastic in an effort to reduce plastic waste. Bananas contain 66% carbohydrates, protein, water and essential minerals . To get biodegradable plastic, starch is added along with CMC (carboxy methylcellulose), glycerol and citronella oil as anti-bacterial and antioxidant. In this research, a research was conducted on the manufacture of biodegradable plastic mixture of starch, carboxy methyl cellulose (CMC), glycerol as a plasticizer and citronella oil by modifying CMC, glycerol and citronella oil. This study includes two variables, namely fixed variables and variable variables. Fixed variables include starch concentration with water 1:5, stirring speed 100 rpm and starch gelatinization temperature 70oC, while variables including CMC concentration include levels (5.5; 6.5 ; and 7.5) % (w/w), Citronella oil concentrations included (15; 20; and 25) % (w/v), and glycerol concentrations included (25; 35; and 45)% (w/v). This study aims to determine the effect of adding CMC citronella oil and glycerol as a plasticizer to the mechanical properties, morphology, and biodegradability tests , as well as the antioxidant activity of the resulting plastic . The results of this study indicate that biodegradable plastic has a tensile strength value of 0.210.38 kgf/mm2; elongation value between 16.3-54.20%; Morphological examination showed that the surface of the plastic was smooth and the plastic completely decomposed in the soil within 27 days. Keywords: Biodegradable plastic, CMC, banana starch.